The Used of English-Indonesian Translation Methods in Hans Christian Anderson’s Short Story “Thumbelina” - Kembaren, Farida Repelita Waty; Afifah, Nabila Yun; Hizbullah, Gilang (EDULIA: English Education, Linguistic and Art Journal, 2024)
This study analyzes the translation process used in the Hans Christian Anderson short story "Thumbelina," which was translated into Indonesian by research participants, students. The researcher applied translation theory, which is based on Newmark Theory, in translation analysis procedures. The researcher saw that there were many different approaches showing up in the translation results, therefore we were interested in finding out what kinds of equivalency translation the participants were doing to improve the target language's readability. This study employed a qualitative descriptive approach that incorporates document analysis and observation. As a result, the researcher discovers that the university students employed six different techniques to translate the short story "Thumbelina" into the target language. Literal Method was employed by the five participants the most frequently (87 times). Communicative Method came in second place with a total of 72 instances. However, with just 14 translation methods utilized, Free Translation was the least popular option among the participants. In contrast, the participants employed the word-for-word technique 43 times, the adaptation method 42 times, and the faithful method 26 times. In this case, the students translated the narrative text using multiple approaches. This study is useful for teaching and learning practice as the research highlight the importance of considering target language readability when translating literary works from the source language. Keywords: Narrative, Newmark, Translation Methods, University Students